混凝土搅拌车专用减速机的静强度试验研究 - 李荣满; 张跃春; 李焱; 余玉西; 何园园 (Jixie chuandong)
To test the static strength of the speed reducer,the reducer load conditions are calculated and analyzed.The detail test scheme is formulated and the special frock clamp for loading is designed.By using hydraulic torque loader and hydraulic loading oil cylinder,the simulated loading for the reducer are carried out.The strain on some key points in reducer are measured.The test results show that,each measured point stress is less than the allowable stress and agrees basically with the results obtained by finite element calculation.It is found that the static strength of the reduce can satisfy the design requirements and a basis for optimal design is provided by the test result.